Reliability of maintained systems subjected to wear failure mechanisms : theory and applications - Bayle, Franck (Mechanical engineering and solid mechanics series., 2019)
Today, the reliability of systems has become a major issue in most industrial applications. The theoretical approach to estimating reliability was largely developed in the 1960s for maintenance-free systems, and more recently, in the late 1990s, it was developed for maintenance-based systems. Customers' expectations concerning reliability (as well as maintenance, safety, etc.) are growing ever more demanding over the generations of systems. However, the theoretical methods used to handle the systems are not suitable when aging mechanisms are present. This book proposes a theoretical approach to estimate all of these quantities correctly. In addition to the theoretical aspect, it details a number of issues that any industrial system will meet sooner or later, whether due to design flaws, the batch of components, manufacturing problems or new technologies that result in the aging of mechanisms during their operational use.